Highly transparent modulated surface textured front electrodes for high‐efficiency multijunction thin‐film silicon solar cells. (16th June 2015) - Tan, Hairen; Moulin, Etienne; Si, Fai Tong; Schüttauf, Jan‐Willem; Stuckelberger, Michael; Isabella, Olindo; Haug, Franz‐Josef; Ballif, Christophe; Zeman, Miro; Smets, Arno H. M.
Abstract To further increase the efficiency of multijunction thin‐film silicon (TF‐Si) solar cells, it is crucial for the front electrode to have a good transparency and conduction, to provide efficient light trapping for each subcell, and to ensure a suitable morphology for the growth of high‐quality silicon layers. Here, we present the implementation of highly transparent modulated surface textured (MST) front electrodes as light‐trapping structures in multijunction TF‐Si solar cells. The MST substrates comprise a micro‐textured glass, a thin layer of hydrogenated indium oxide (IOH), and a sub‐micron nano‐textured ZnO layer grown by low‐pressure chemical vapor deposition (LPCVD ZnO). The bilayer IOH/LPCVD ZnO stack guarantees efficient light in‐coupling and light trapping for the top amorphous silicon (a‐Si:H) solar cell while minimizing the parasitic absorption losses. The crater‐shaped micro‐textured glass provides both efficient light trapping in the red and infrared wavelength range and a suitable morphology for the growth of high‐quality nanocrystalline silicon (nc‐Si:H) layers. Thanks to the efficient light trapping for the individual subcells and suitable morphology for the growth of high‐quality silicon layers, multijunction solar cells deposited on MST substrates have a higher efficiency than those on single‐textured state‐of‐the‐art LPCVD ZnO substrates. Efficiencies of 14.8% (initial) and 12.5% (stable) have been achieved for a‐Si:H/nc‐Si:H tandem solar cells with the MST front electrode, surpassing efficiencies obtained on state‐of‐the‐art LPCVD ZnO, thereby highlighting the high potential of MST front electrodes for high‐efficiency multijunction solar cells. Copyright © 2015 John Wiley & Sons, Ltd.